Considerations for shared decision-making in treatment of chronic rhinosinusitis with nasal polyps - Ramkumar, Shreya P.; Lal, Devyani; Miglani, Amar (Frontiers in Allergy, 2023)
Shared decision-making is an approach where physicians and patients work together to determine a personalized treatment course. Such an approach is integral to patient-centered care in chronic rhinosinusitis with nasal polyps (CRSwNP). CRSwNP is a chronic inflammatory condition of the sinonasal cavity that can severely impact physical health, smell, and quality of life (QOL). Traditional standard-of-care treatment options include topical (i.e. sprays) and oral corticosteroids and endoscopic sinus surgery, but more recently, novel corticosteroid delivery methods (i.e. high volume irrigations, recently-approved exhalation breath-powered delivering devices, and drug-eluting steroid implants) and 3 new FDA approved biologics directed against type II immunomodulators have become available. The availability of these therapeutics offers exciting new opportunities in CRSwNP management but requires personalized and shared-decision making as each modality has variable impacts on CRSwNP and related comorbid conditions. Studies have published treatment algorithms, but the practical use of these lean guidelines is heavily influenced by the lens of the treating physician, the most common being otolaryngologists and allergy immunologists. Clinical equipoise occurs when there is no basis for one intervention to be regarded as “better” than another. While most guidelines, in general, support the use of topical corticosteroids with or without oral corticosteroids followed by ESS for the majority of unoperated CRSwNP patients, there are situations of clinical equipoise that arise particularly in CRSwNP who have failed surgery or those with severe comorbid conditions. In the shared decision-making process, clinicians and patients must consider symptomatology, goals, comfort, compliance, treatment efficacy, and treatment cost when determining the initial choice of therapy and escalation of therapy with the potential use of multiple modalities for recalcitrant CRSwNP. A summary of salient considerations that might constitute shared decision-making is presented in this summary.